Public Value Layanan Gawat Darurat “SIAGA BRO PSC 119” di Kabupaten Bojonegoro - Rosyidah, Laely; Harmawan, Bagus Nuari (Kolaborasi : Jurnal Administrasi Publik, 2025)
SIAGA BRO PSC 119 attend to provide a rapid response to medical emergencies, which must be available in Bojonegoro District, which operates under the auspices of the Bojonegoro District Health Office. Till now, it has handled over 2,000 emergency cases since its establishment three years ago. However, this emergency service still faces challenges, including a lack of public understanding and an unstable increase in the number of users. When linked to the number of emergency situations, such as accidents, the number of emergency calls should increase in line with the number of accidents occurring. The purpose of this study is to determine the public value of the SIAGA BRO PSC 119 service provided by the Bojonegoro District Health Office, using a descriptive qualitative method through interviews with relevant parties and several users who have used the SIAGA BRO PSC 119 service, and analyzed to determine public value through the measurement dimensions by Faulkner & Kaufman (2018), including Outcome Achievement, Trust and Legitimacy, Service Delivery Quality, and Efficiency. The results indicate that the SIAGA BRO PSC 119 service has a fairly good quality of service delivery and achieves a relatively high level of public trust, particularly in terms of economic, social, and cultural outcomes. However, reporting incidents by the network to the central office is still hindered due to insufficient resources, and active outreach efforts are still a concern raised by the community.